Comparative transcriptome analysis revealed differential gene expression involved in wheat leaf senescence between stay-green and non-stay-green cultivars - Li, Qing; Yang, Huai; Guo, Jingwei; Huang, Qianglan; Zhong, Shengfu; Tan, Feiquan; Ren, Tianheng; Li, Zhi; Chen, Chen; Luo, Peigao (Frontiers in Plant Science, 2022)
Breeders agree that leaf senescence is a favorable process for wheat seed yield improvement due to the remobilization of leaf nutrients. However, several studies have suggested that staying green may be an important strategy for further increasing wheat yields. In this study, we performed a comparative transcriptome analysis between wheat cultivars CN17 and CN19 after heading and also measured photosynthetic parameters, chlorophyll (Chl) contents, and antioxidant enzyme activities at various time points after heading. The physiological and biochemical indexes revealed that CN17 exhibited a functionally stay-green phenotype while CN19 did not. We identified a total of 24,585 and 34,410 differential expression genes between genotypes at two time-points and between time-points in two genotypes, respectively, and we also found that 3 (37.5%) genes for leaf senescence, 46 (100%) for photosynthesis - antenna protein, 33 (70.21%) for Chl metabolism and 34 (68%) for antioxidative enzyme activity were upregulated in CN17 compared with CN19 during leaf senescence, which could be regulated by the differential expression of SAG39 (senescence-associated gene 39), while 22 (100%) genes for photosynthesis - antenna proteins, 6 (46.15%) for Chl metabolism and 12 (80%) for antioxidative enzyme activity were upregulated in CN17 compared with CN19 before the onset of leaf senescence. Here, we further clarified the expression profiles of genes associated with a functional stay-green phenotype. This information provides new insight into the mechanism underlying delayed leaf senescence and a new strategy for breeders to improve wheat yields.